2021
DOI: 10.3390/molecules26154630
|View full text |Cite
|
Sign up to set email alerts
|

Amber Extract Reduces Lipid Content in Mature 3T3-L1 Adipocytes by Activating the Lipolysis Pathway

Abstract: Amber—the fossilized resin of trees—is rich in terpenoids and rosin acids. The physiological effects, such as antipyretic, sedative, and anti-inflammatory, were used in traditional medicine. This study aims to clarify the physiological effects of amber extract on lipid metabolism in mouse 3T3-L1 cells. Mature adipocytes are used to evaluate the effect of amber extract on lipolysis by measuring the triglyceride content, glucose uptake, glycerol release, and lipolysis-related gene expression. Our results show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 37 publications
0
10
0
1
Order By: Relevance
“…In previous studies, many effects of amber—such as anti-allergic effects [ 17 ], promotion of collagen production, and suppression of melanin production [ 19 ]—have been investigated. In our previous studies, we found that amber extract also has anti-inflammatory effect [ 18 ], the ability to reduce fat accumulation [ 20 ], and can protect cells from amyloid-β1-42-induced cytotoxicity [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, many effects of amber—such as anti-allergic effects [ 17 ], promotion of collagen production, and suppression of melanin production [ 19 ]—have been investigated. In our previous studies, we found that amber extract also has anti-inflammatory effect [ 18 ], the ability to reduce fat accumulation [ 20 ], and can protect cells from amyloid-β1-42-induced cytotoxicity [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Russia, amber is commonly used in folk medicine [ 16 ]. In recent years, the effects of amber on allergy [ 17 ], anti-inflammation [ 18 ], suppression of melanin production, promotion of collagen production [ 19 ], and reduction in fat accumulation [ 20 ] have been identified. A previous study by our group found that amber extract has a protective effect against amyloid-β-induced neuronal cell death [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, Nile red assay was employed to give an idea of the general lipid reducing ability of AE in C. elegans. Extensive research has already been conducted by Sogo et al, 2021 (from our laboratory) on the lipolytic effect of AE on 3T3-L1 adipocytes where Oil Red O (recommended by O'Rourke et al, 2009) was employed [12].…”
Section: Discussionmentioning
confidence: 99%
“…Amber is a brownish gum-like tree resin from the Sciadopityaceae family that has fossilized over time. It contains succinic acid [11] and many phytochemicals including terpenoids [12,13]. Terpenoids have been highlighted to possess an antioxidant ability and offer protection against oxidative stress-induced diseases such as cancers, diabetes, neurodegenerative diseases and many others [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation